Pola Sintaksis pada Puji-Pujian Bahasa Jawa: Analisis Tipologi Bahasa - Anton Anton; Sueb Sueb; Sultan Tirta Mujtaba; Tadkiroatun Musfiroh; Setyawan Pujiono (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study aims to analyze syntactic patterns in Javanese praises (puji-pujian) through the lens of language typology. Puji-pujian is a form of Islamic oral tradition typically recited between the adhan and iqamah in mosques, predominantly in Java. The data were collected from five Javanese praises recited at mosques in the Langensari-Banjar area using listening and note-taking techniques (simak catat). The study employs a descriptive qualitative method with a structural-linguistic approach, and data analysis was conducted using the distributional method (metode agih). The theoretical framework draws on Greenberg's (1963) and Comrie's (1989) typological theory, focusing on the constituent order of Subject (S), Verb/Predicate (V), and Object (O). The findings reveal that although the basic typological pattern of Javanese is SVO, the puji-pujian corpus demonstrates significant variation, including SV, VO, VSO, VOS, VOK, and nominal predicate patterns (SPel). This variation is primarily driven by aesthetic demands—including meter and rhyme—and the pragmatic function of emphasis in sacred discourse. The results indicate that poetic and religious registers systematically trigger syntactic inversion in Javanese oral tradition. Abstrak Penelitian ini bertujuan untuk menganalisis pola sintaksis pada puji-pujian bahasa Jawa melalui kajian tipologi bahasa. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan linguistik struktural. Data dikumpulkan dari lima puji-pujian berbahasa Jawa yang dikumandangkan di masjid-masjid wilayah Langensari-Banjar menggunakan teknik simak dan catat. Analisis data dilakukan menggunakan metode agih (distribusional). Kerangka teori mengacu pada teori tipologi Greenberg (1963) dan Comrie (1989) yang berfokus pada urutan konstituen Subjek (S), Verba/Predikat (V), dan Objek (O). Temuan menunjukkan bahwa meskipun pola tipologi dasar bahasa Jawa adalah SVO, korpus puji-pujian memperlihatkan variasi yang signifikan, meliputi pola SV, VO, VSO, VOS, VOK, dan predikat nominal (SPel). Variasi ini terutama didorong oleh tuntutan estetika—termasuk metrum dan rima serta fungsi pragmatis penekanan dalam wacana sakral. Hasil penelitian mengindikasikan bahwa register puitis dan religius secara sistematis memicu inversi sintaksis dalam tradisi lisan Jawa.